Moving to remote learning in adult education: Challenges and solutions of limited technological resources and capabilities - Durgunoğlu, Aydin Yücesan; Cantürk, Meltem; Kaya, Uğur; Yazıcı, Betül; Şahin, Kübranur (Frontiers in Education, 2022)
The Covid pandemic has caused disruptions in educational systems, hence educators have developed innovative ways to address this new reality. Around the world, many adult education programs try to reach women who could not cannot complete their education because of poverty and sociocultural, especially patriarchal barriers. COVID was especially challenging for such lifelong learning programs because they operate with limited technological resources and work with learners with weaker digital proficiencies. In this paper, we describe how we rapidly adapted our face-to-face empowerment program for women to remote learning. We describe what we did and the outcomes as evaluated by pre- and post-tests, participant observations and interviews. We finish by summarizing the successes and challenges of addressing this new reality in education.